2021
DOI: 10.3390/cancers13123014
|View full text |Cite
|
Sign up to set email alerts
|

Upper Aerodigestive Tract Squamous Cell Carcinomas Show Distinct Overall DNA Methylation Profiles and Different Molecular Mechanisms behind WNT Signaling Disruption

Abstract: Upper aerodigestive tract (UADT) tumors present different biological behavior and prognosis, suggesting specific molecular mechanisms underlying their development. However, they are rarely considered as single entities (particularly head and neck subsites) and share the most common genetic alterations. Therefore, there is a need for a better understanding of the global DNA methylation differences among UADT tumors. We performed a genome-wide DNA methylation analysis of esophageal (ESCC), laryngeal (LSCC), oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Methylome analysis was performed as previously described [ 19 ]. Briefly, DNA was extracted from ESCC and HNSCC tumors and their respective non-tumor adjacent tissues (NTST), all snap-frozen, with the DNeasy Blood & Tissue Kit (Qiagen, Hilden, Germany), as follows: 16 NTST and 24 ESCC; 12 NTST and 20 LSCC; seven NTST and 15 OCSCC; and 8 OPSCC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylome analysis was performed as previously described [ 19 ]. Briefly, DNA was extracted from ESCC and HNSCC tumors and their respective non-tumor adjacent tissues (NTST), all snap-frozen, with the DNeasy Blood & Tissue Kit (Qiagen, Hilden, Germany), as follows: 16 NTST and 24 ESCC; 12 NTST and 20 LSCC; seven NTST and 15 OCSCC; and 8 OPSCC.…”
Section: Methodsmentioning
confidence: 99%
“…Tumors from the upper aerodigestive tract (UAT) show few recurrently mutated genes, suggesting that other molecular mechanisms take part in their development. In these tumors, DNA methylation is intricately linked with risk-factor exposure [ 18 ] and malignant transformation [ 19 ]. The esophagus (ESCC) and, among the head and neck organs, the oral cavity (OCSCC), larynx (LSCC) and oropharynx (OPSCC) are most commonly affected by squamous cell carcinomas [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the few common genetic alterations found in HNSCC generally, DNA methylation shows more frequent and subsite-specific changes, an important asset for molecular diagnosis [24,212,213,234]. P16INK4A is hypermethylated in 27-44% of HNSCC [93,97,98,235]; however, it has already been reported that almost half of the samples could not be analyzed due to loss of heterozygosity [98,236].…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…Although differences according to tumor site and associated risk factors exist, these only partially explain this heterogeneity. In this context, epigenetic alterations have gained attention due to their frequency and site-specific pattern [23][24][25][26], being promising biomarkers. In the following sections, we bring together the current knowledge on alterations of DNA methylation and microRNA expression in HNSCC natural history, focusing on how they contribute to each step of the process and on their applicability as biomarkers of exposure, HNSCC development, progression, and response to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Existing research has suggested that epigenetics takes on a critical significance to LSCC development and progression 10 . DNA methylation refers to one of the most characteristic epigenetic modifications, and it is capable of regulating gene transcription.…”
Section: Introductionmentioning
confidence: 99%